Gestational and Postnatal Exposure to a Contaminant Mixture: Effects on Estrogen Receptor Protein Expression In the Postpartum Maternal Brain - Konji, Sandra (Université d'Ottawa / University of Ottawa, 2019)
Maternal behaviours are those that increase offspring survival. Estrogens affect maternal behaviour by activating Estrogen Receptors (ER) in the brain. Maternal brain plasticity was explored by characterizing the effects of exposure to a mixture of environmental pollutants on number of ERs. Following exposure to the toxicants during pregnancy and lactation, brains of female rats were collected, sectioned at 30 μm and immunohistochemistry for ERα performed. Immuno-positive cells in the mPOA, VTA and NAc were counted. A two way ANOVA revealed no main effect of Treatment on the number of immunopositive cells for all three brain regions. However, a significant difference between the High and Low Doses with the high dose reducing the number of ERα+ cells in the mPOA and VTA. Our work showcases the importance of studying the effects of multiple chemical co-exposures on the mother's brain, as maternal brain changes impact maternal behaviour consequently affecting offspring neurodevelopment.
Keywords: maternal behaviour; Estrogen Receptors; Toxicant Mixture; Methyl Mercury; Medial Preoptic Area; Nucleus Accumbens; Ventral Tegmental Area